Near-real time crop loss assessment for crop insurance in India - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
CCAFS has developed a system-analytical tool (Crop-Loss Assessment Monitor (CAM)), which integrates crop growth simulation models, Geographic Information System (GIS), spatial weather data, and remote sensing for crop growth monitoring and yield losses occurring due to extreme events. The results indicate the wide applicability of CAM tool for policy design, increasing efficacy and effectiveness of crop insurance programs at the sub-national level. Many insurance companies and other stakeholders have shown a keen interest in using this tool.